Circulating miRNAs Associated With ER Stress and Organ Damage in a Preclinical Model of Trauma Hemorrhagic Shock - Luís, Andreia (Front Med (Lausanne), 2020)
Circulating microRNAs (miRNA) alterations have been reported in severe trauma patients but the pathophysiological relevance of these changes is still unclear. miRNAs are critical biologic regulators of pathological events such as hypoxia and inflammation, which are known to induce endoplasmic reticulum (ER) stress. ER stress is emerging as an important process contributing to the development of single and/or multiple organ dysfunction after trauma hemorrhagic shock (THS) accompanied by impaired tissue microcirculation and inflammation. Here, we aim to bring new insights into the involvement of miRNAs associated with ER stress in THS. THS was induced in rats by a median laparotomy and blood withdrawal until mean arterial pressure (MAP) dropped to 30-35 mmHg followed by a restrictive (40 min) and full reperfusion (60 min) with Ringer's solution. Tunicamycin was used to induce ER stress. Blood samples were collected 24 h after THS for the determination of pathological changes in the blood (PCB) and circulating miRNAs. Plasma levels of circulating miRNAs were compared between THS, tunicamycin, and sham groups and correlated to biomarkers of PCB. MiRNA profile of THS animals showed that 40 out of 91 (44%) miRNAs were significantly upregulated compared to sham (p < 0.01). The data showed a very strong correlation between liver injury and miR−122-5p (r = 0.91, p < 0.00001). MiR-638, miR−135a-5p, miR−135b-5p, miR-668-3p, miR-204-5p, miR−146a-5p, miR−200a-3p, miR−17-5p, miR−30a-5p, and miR−214-3p were found positively correlated with lactate (r > 0.7, p < 0.05), and negatively with base excess (r ≤ 0.8, p < 0.05) and bicarbonate (r ≤ 0.8, p < 0.05), which are clinical parameters that reflected the shock severity. Tunicamycin significantly modified the microRNA profile of the animals, 33 out of 91 miRNAs were found differentially expressed. In addition, principal component analysis revealed that THS and tunicamycin induced similar changes in plasma miRNA patterns. Strikingly, the data showed that 15 (25.9%) miRNAs were regulated by both THS and tunicamycin (p < 0.01). This included miR−122-5p, a liver-specific microRNA, but also miR−17-5p and miR-125b-5p which are miRNAs remarkably involved in unfolded protein response (UPR)-mediating pro-survival signaling (IRE1α). Since miRNAs associated with ER stress are clearly correlated with THS, our data strongly suggest that interaction between miRNAs and ER stress is an important pathologic event occurring during THS. Overall, we consider that the miRNA profile developed in this study can provide a rationale for the development of bench-to-bedside strategies that target miRNAs in critical care diseases or be used as biomarkers in the prognosis of trauma patients.